Active ester, curable resin composition, and cured product

The network structure is formed by reacting the active ester and the epoxy resin, which solves the problems of high thermal resistance, low dielectric and high elasticity of the semiconductor packaging substrate, and achieves the improvement of the high performance of the material.

JP7625940B2Active Publication Date: 2025-02-04DIC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021061291
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-02-04
Estimated Expiration
2041-03-31

Smart Images

  • Figure 0007625940000008
    Figure 0007625940000008
  • Figure 0007625940000009
    Figure 0007625940000009
  • Figure 0007625940000010
    Figure 0007625940000010
Patent Text Reader

Abstract

To provide an active ester which gives a cured product that can exhibit high heat resistance, low dielectric characteristics (low dielectric constant and low dielectric loss tangent), and high elastic modulus, a curable resin composition containing the active ester, a cured product obtained using the curable resin composition, and a circuit board using the curable resin composition.SOLUTION: An active ester is obtained by reacting an aromatic compound (a) having two hydroxyl groups at adjacent positions on an aromatic ring, an aromatic monohydroxy compound (b), and an aromatic compound having two or more carboxyl groups and / or its acid halide or esterified product (c).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active ester, a curable resin composition containing the active ester, and a cured product obtained from the curable resin composition. [Background technology]

[0002] Epoxy resin compositions containing an epoxy resin and a curing agent therefor as essential components exhibit excellent heat resistance and insulating properties in the cured product, and are therefore widely used in electronic component applications such as semiconductors and multilayer printed circuit boards.

[0003] Among these electronic component applications, semiconductor package substrates are becoming thinner and thinner. However, warping of the package substrate during mounting is becoming an issue, so there is a demand for high heat resistance and a high elastic modulus to suppress warping of the package substrate.

[0004] Meanwhile, in recent years, signals have become faster and higher in frequency even in semiconductor package substrates, and it is desired to provide a curable resin composition capable of obtaining a cured product that exhibits a sufficiently low dielectric tangent while maintaining a sufficiently low dielectric constant even for high-speed and high-frequency signals.

[0005] In response to these demands, a technique is known in which an active ester compound is used as a curing agent for epoxy resin as a material capable of realizing a low dielectric constant and a low dielectric loss tangent (see Patent Document 1).

[0006] However, the properties of low dielectric constant and low dielectric loss tangent in Patent Document 1 are insufficient to meet recent demands, and the heat resistance does not meet the demands. Also, in order to meet the demands for miniaturization and thinning, a high elastic modulus is required. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2004-169021 A Summary of the Invention [Problem to be solved by the invention]

[0008] Therefore, an object of the present invention is to provide an active ester capable of imparting high heat resistance, low dielectric properties (low dielectric constant and low dielectric tangent), and high elastic modulus to the obtained cured product, a curable resin composition containing the active ester, a cured product obtained using the curable resin composition, and further a circuit board and the like using the curable resin composition. [Means for solving the problem]

[0009] Therefore, the present inventors conducted extensive research to solve the above problems and discovered that by using a specific active ester in a curable resin composition, the resulting cured product exhibits excellent high heat resistance, low dielectric properties (low dielectric constant and low dielectric tangent), and high elastic modulus, thereby completing the present invention.

[0010] That is, the present invention relates to an active ester obtained by reacting (a) an aromatic compound having two hydroxyl groups at adjacent positions on an aromatic ring, (b) an aromatic monohydroxy compound, and (c) an aromatic compound having two or more carboxyl groups and / or an acid halide or ester thereof.

[0011] In the active ester of the present invention, the aromatic compound (a) is preferably at least one compound selected from the group consisting of the following general formulas (1) to (3). [ka] (In the above formula, each R independently represents a hydrocarbon group having 1 to 10 carbon atoms, n represents an integer of 0 to 4, and m represents an integer of 0 to 2.)

[0012] The present invention relates to a curable resin composition containing the active ester and an epoxy resin.

[0013] The present invention relates to a cured product obtained by subjecting the curable resin composition to a curing reaction.

[0014] The present invention relates to a prepreg comprising a reinforcing substrate and a semi-cured product of the curable resin composition impregnated into the reinforcing substrate.

[0015] The present invention relates to a circuit board obtained by laminating the prepreg and copper foil and subjecting the laminate to thermocompression molding.

[0016] The present invention relates to a build-up film comprising the above-mentioned curable resin composition.

[0017] The present invention relates to a semiconductor encapsulant comprising the above-mentioned curable resin composition.

[0018] The present invention relates to a semiconductor device comprising a cured product obtained by heat-curing the semiconductor encapsulant. Effect of the Invention

[0019] According to the present invention, it is possible to provide an active ester capable of imparting excellent high heat resistance, low dielectric properties (low dielectric constant and low dielectric tangent), and high elastic modulus to the obtained cured product, a curable resin composition containing the active ester, and a cured product obtained using the curable resin composition, as well as a semiconductor encapsulating material, a semiconductor device, a prepreg, a circuit board, a build-up film, and the like, which are each made using the curable resin composition, and these are useful. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] [Active ester] The present invention relates to an active ester obtained by reacting (a) an aromatic compound having two hydroxyl groups at adjacent positions on an aromatic ring, (b) an aromatic monohydroxy compound, and (c) an aromatic compound having two or more carboxyl groups and / or an acid halide or ester thereof. By using the active ester, a cured product having high heat resistance, low dielectric properties (low dielectric constant, low dielectric loss tangent), and high elastic modulus can be obtained, which is preferable. The reason why such properties are obtained is not necessarily clear, but by using an aromatic compound (a) (e.g., catechol) having two hydroxyl groups at adjacent positions on the aromatic ring as a raw material for the active ester, ester groups based on the two hydroxyl groups of the aromatic compound (a) having two hydroxyl groups at adjacent positions on the aromatic ring are formed at adjacent positions on the aromatic ring (e.g., benzene ring), and the crosslinking points of the cured product are adjacent, and the molecular motion is inhibited by the steric hindrance, thereby expressing high heat resistance and high elastic modulus. In addition, the active ester can react with the epoxy resin to form a network structure without secondary hydroxyl groups, which are polar groups, and therefore can express a sufficiently low dielectric constant and dielectric loss tangent.

[0021] [Aromatic compound (a) having two hydroxyl groups at adjacent positions on the aromatic ring] The activated ester of the present invention is characterized in that it is obtained by reacting an aromatic compound (a) having two hydroxyl groups at adjacent positions on an aromatic ring (hereinafter, sometimes referred to as "aromatic compound (a)"). Note that the "two hydroxyl groups at adjacent positions on an aromatic ring" means "two hydroxyl groups bonded to two adjacent carbon atoms on an aromatic ring".

[0022] In the active ester of the present invention, the aromatic compound (a) is preferably at least one compound selected from the group consisting of the following general formulas (1) to (3): Since the hydroxyl groups are adjacent to each other on the aromatic ring of the compound, the ester groups contained in the obtained active ester are also adjacent to each other, and the crosslinking points of the cured product obtained using the active ester are adjacent to each other, and the molecular motion is inhibited by the steric hindrance, which is preferable because it can exhibit high heat resistance and high elastic modulus. [ka]

[0023] In the above formulas (1) to (3), each R is preferably independently a hydrocarbon group having 1 to 10 carbon atoms. Examples of the hydrocarbon group include a methyl group, an ethyl group, a propyl group, a butyl group, an allyl group, and a benzyl group. From the viewpoint of high heat resistance and a low dielectric tangent, it is preferable that the R is unsubstituted, and from the viewpoint of a low dielectric constant, it is preferable that the R is a butyl group.

[0024] In the above formulas (1) to (3), n is preferably an integer of 0 to 4, and more preferably an integer of 0 to 1. When the n is within the above range, high heat resistance, low dielectric tangent, and low dielectric constant are achieved, which is preferable.

[0025] In the above formulas (1) to (3), m is preferably an integer of 0 to 2, and more preferably an integer of 0 to 1. When m is within the above range, high heat resistance, low dielectric tangent, and low dielectric constant are achieved, which is preferable.

[0026] In addition, it is preferable to use a compound containing a catechol skeleton (catechol compound) as the aromatic compound (a), and more specifically, it is more preferable to use a catechol compound such as catechol or tertiary butyl catechol. The obtained cured product can be made to have high heat resistance, low dielectric properties (low dielectric constant, low dielectric tangent), and high elastic modulus, which is preferable. By introducing a catechol skeleton based on the aromatic compound (a) into the active ester, the ester groups in the active ester form a structure adjacent to each other on the same aromatic ring, so that steric hindrance becomes large compared to the conventional design, molecular motion is suppressed, and the obtained cured product has low dielectric properties (low dielectric constant, low dielectric tangent) and can have a high elastic modulus. In addition, the active ester can react with an epoxy resin to form a network structure without a secondary hydroxyl group, which is a polar group, so that the obtained cured product can exhibit a sufficiently low dielectric constant and dielectric tangent.

[0027] The catechol is a dihydroxybenzene having hydroxyl groups at the 1- and 2-positions, and may be a catechol compound having an alkyl group such as a methyl group as a substituent on the aromatic ring of the catechol.

[0028] In addition, from the viewpoint of imparting high heat resistance, it is preferable to use a catechol compound that does not have a substituent on the aromatic ring (for example, catechol). In addition, from the viewpoint of low dielectric properties, it is preferable to use a catechol compound having an alkyl group with 4 to 10 carbon atoms, such as catechol having a tertiary butyl group (tertiary butyl catechol). If the number of carbon atoms is 4 or more, the low dielectric properties can be sufficiently obtained, and if the number of carbon atoms is 10 or less, it is preferable to prevent a decrease in reactivity during the synthesis of an active ester due to steric hindrance.

[0029] The aromatic compound (a) may be used alone or in combination with a plurality of compounds having alkyl groups, such as methyl groups, at different positions.

[0030] [Aromatic monohydroxy compounds (b)] The present invention is characterized in that it is obtained by reacting an aromatic monohydroxy compound (b). By using the aromatic monohydroxy compound (b), the aromatic monohydroxy compound (b) acts as an end-capping agent during the synthesis of the active ester, thereby controlling the molecular weight distribution and optimizing the viscosity of the active ester.

[0031] The aromatic monohydroxy compound (b) is not particularly limited, and examples thereof include alkylphenols such as phenol, o-cresol, m-cresol, p-cresol, 2,4-xylenol, 2,6-xylenol, and tertiary butylphenol; aralkylphenols such as o-phenylphenol, p-phenylphenol, 2-benzylphenol, 4-benzylphenol, styrenated phenol, and 4-(α-cumyl)phenol; and naphthol compounds such as α-naphthol (1-naphthol) and β-naphthol (2-naphthol). These may be used alone or in combination of two or more. Among them, tertiary butylphenol and α-naphthol are preferred because they provide a cured product with excellent heat resistance and dielectric properties (low dielectric properties).

[0032] [Aromatic compounds having two or more carboxyl groups and / or their acid halides or esters (c)] The present invention is characterized in that it is obtained by reacting an aromatic compound having two or more carboxyl groups and / or its acid halide or ester (c) (hereinafter, sometimes referred to as "aromatic compound (c)"). By using the aromatic compound (c), a cured product with excellent heat resistance can be obtained, which is preferable.

[0033] The aromatic compound (c) is not particularly limited, and examples thereof include compounds having two or more carboxyl groups in a substituted or unsubstituted aromatic ring. The "carboxyl group" includes carboxyl group; halogenated acyl groups such as fluorinated acyl group, chlorinated acyl group, and brominated acyl group; alkyloxycarbonyl groups such as methyloxycarbonyl group and ethyloxycarbonyl group; and aryloxycarbonyl groups such as phenyloxycarbonyl group and naphthyloxycarbonyl group. When the aromatic compound has a halogenated acyl group, the aromatic compound is an acid halide, and when the aromatic compound has an alkyloxycarbonyl group or an aryloxycarbonyl group, the aromatic compound can be an ester. Among these, the aromatic compound preferably has a carboxyl group, a halogenated acyl group, or an aryloxycarbonyl group, more preferably has a carboxyl group or a halogenated acyl group, and even more preferably has a carboxyl group, a chloride acyl group, or a bromide acyl group.

[0034] The aromatic ring is not particularly limited, but examples thereof include a monocyclic aromatic ring, a condensed aromatic ring, an aromatic ring consisting of multiple rings, and an aromatic ring connected by an alkylene chain.

[0035] Examples of the aromatic compound (c) include, but are not limited to, benzene dicarboxylic acids such as isophthalic acid, terephthalic acid, 5-allyl isophthalic acid, and 2-allyl terephthalic acid; benzene tricarboxylic acids such as trimellitic acid and 5-allyl trimellitic acid; naphthalene dicarboxylic acids such as naphthalene-1,4-dicarboxylic acid, naphthalene-1,5-dicarboxylic acid, naphthalene-2,3-dicarboxylic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, 3-allylnaphthalene-1,4-dicarboxylic acid, and 3,7-diallylnaphthalene-1,4-dicarboxylic acid; pyridine tricarboxylic acids such as 2,4,5-pyridine tricarboxylic acid; triazine carboxylic acids such as 1,3,5-triazine-2,4,6-tricarboxylic acid; and acid halides and esters thereof. Among these, benzenedicarboxylic acid and benzenetricarboxylic acid are preferred, isophthalic acid, terephthalic acid, isophthalic acid chloride, terephthalic acid chloride, 1,3,5-benzenetricarboxylic acid, and 1,3,5-benzenetricarbonyl trichloride are more preferred, and bis(chlorocarbonyl)benzenes such as isophthalic acid chloride and terephthalic acid chloride, and 1,3,5-benzenetricarbonyl trichloride are even more preferred.

[0036] Among the above, from the viewpoint of the heat resistance and dielectric properties of the obtained cured product being good, and the industrial availability and workability of the raw materials, aromatic compounds having a monocyclic aromatic ring, aromatic compounds having a condensed aromatic ring, etc. are preferred, benzenedicarboxylic acid, benzenetricarboxylic acid, naphthalene dicarboxylic acid, and acid halides thereof are preferred, benzenedicarboxylic acid, naphthalene dicarboxylic acid, and acid halides thereof are more preferred, and isophthalic acid, terephthalic acid, naphthalene-1,5-dicarboxylic acid, naphthalene-2,3-dicarboxylic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, 1,3,5-benzenetricarboxylic acid, and acid halides thereof are even more preferred. The above-mentioned aromatic compounds (c) may be used alone or in combination of two or more.

[0037] The active ester of the present invention functions as a curing agent for epoxy resins, etc., and can impart high heat resistance, low dielectric properties (low dielectric constant, low dielectric tangent), and high elastic modulus to the cured product obtained by using the active ester, which is a preferred embodiment. In addition, the generation of hydroxyl groups can be prevented or suppressed during the reaction of the active ester with the epoxy resin, making it useful because of its excellent low dielectric properties.

[0038] By using the active ester of the present invention, a cured product having low dielectric properties and excellent heat resistance and high elastic modulus can be obtained, which is a preferred embodiment. The reason is not necessarily clear, but by introducing a catechol skeleton based on the aromatic compound (a) into the active ester, the ester groups in the active ester form a structure adjacent to each other on the same aromatic ring, which increases steric hindrance compared to conventional designs, suppresses molecular motion, and the resulting cured product has low dielectric properties (low dielectric constant, low dielectric loss tangent) and can have a high elastic modulus. In addition, the active ester can react with an epoxy resin to form a network structure without a secondary hydroxyl group, which is a polar group, and can therefore exhibit a sufficiently low dielectric constant and dielectric loss tangent.

[0039] In addition, since the active ester has two or more ester bonds having reactive activity with the epoxy groups of the epoxy resin described below, the crosslink density of the cured product can be increased and the heat resistance can be improved.

[0040] From the viewpoint of achieving a better balance between handleability when preparing a curable resin composition described later and the heat resistance and dielectric properties of the cured product, the active ester preferably has a softening point of 200° C. or less, more preferably 180° C. or less, even more preferably 160° C. or less, and particularly preferably 140° C. or less.

[0041] The reaction with the aromatic compound (a), the aromatic monohydroxy compound (b), and the aromatic compound (c) (hereinafter sometimes referred to as "raw material compound") is not particularly limited, but for example, the aromatic compound (a) and the aromatic monohydroxy compound (b) are mixed and dissolved, and then the aromatic compound (c) is further mixed and dissolved, and the reaction can be carried out in the presence of an alkali catalyst at a temperature of 60°C or less for a reaction time of 1 to 24 hours. Examples of the alkali catalyst that can be used here include sodium hydroxide, potassium hydroxide, triethylamine, pyridine, etc. These may be used alone or in combination of two or more. Among these, sodium hydroxide or potassium hydroxide is preferred because of its high reaction efficiency. These catalysts may be used as an aqueous solution of 3 to 30 mass %. In addition, in order to increase the reaction efficiency, a phase transfer catalyst may be used at this time. For example, alkyl ammonium salts, crown ethers, etc. may be used. These may be used alone or in combination of two or more.

[0042] The reaction is preferably carried out in an organic solvent because the reaction control is easy. Examples of the organic solvent used here include hydrocarbon solvents such as pentane and hexane, ketone solvents such as acetone, methyl ethyl ketone, and cyclohexanone, ether solvents such as diethyl ether and tetrahydrofuran, acetate ester solvents such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate, carbitol solvents such as cellosolve and butyl carbitol, aromatic hydrocarbon solvents such as toluene and xylene, dimethylformamide, dimethylacetamide, and N-methylpyrrolidone. These may be used alone or in the form of a mixed solvent of two or more kinds.

[0043] The reaction ratio of the raw material compounds can be appropriately changed according to the desired molecular design, but from the viewpoint of reducing unreacted terminals and reducing excess reaction raw materials, the aromatic compound (a) is preferably in the range of 0.5 to 5 moles, more preferably 1 to 4 moles, and even more preferably 2 to 3 moles, relative to 1 mole of the aromatic monohydroxy compound (b). Also, the aromatic compound (c) is preferably in the range of 0.5 to 5 moles, more preferably 1 to 4 moles, and even more preferably 2 to 3 moles, relative to 1 mole of the aromatic monohydroxy compound (b).

[0044] After the reaction is completed, when an aqueous solution is used in the presence of an alkali catalyst, the reaction solution is allowed to stand and separated to remove the aqueous layer, and the remaining organic layer is washed with water. This washing is repeated until the aqueous layer becomes nearly neutral (pH 7 or so), thereby reducing the content of inorganic salts that adversely affect the insulating properties, and the activated ester of the present invention can be obtained. After the reaction is completed, the excess raw material compound is removed by drying under heating and reduced pressure, and a high-purity activated ester can be obtained.

[0045] The functional group equivalent of the active ester of the present invention, when the total number of aromatic ester groups in the active ester structure is taken as the number of functional groups of the active ester, is preferably in the range of 100 to 500 g / equivalent, more preferably in the range of 110 to 400 g / equivalent, and further more preferably in the range of 120 to 300 g / equivalent, since a cured product having excellent curability and low dielectric constant and dielectric tangent (low dielectric properties) can be obtained.

[0046] The number average molecular weight (Mn) of the active ester of the present invention is preferably 500 to 3000, and more preferably 600 to 2000. A number average molecular weight (Mn) of 500 or more is preferable because of excellent dielectric properties and heat resistance. On the other hand, a number average molecular weight (Mn) of 3000 or less is preferable because of excellent moldability.

[0047] <Curable resin composition> The present invention relates to a curable resin composition containing the active ester and an epoxy resin. In the curable resin composition, the active ester functions as a curing agent for epoxy resin (or other resins), and a cured product obtained by using the active ester and the epoxy resin can have high heat resistance, low dielectric properties (low dielectric constant, low dielectric tangent), and high elastic modulus, which is a preferred embodiment. In addition, during the reaction between the active ester and the epoxy resin, the generation of hydroxyl groups can be prevented or suppressed, and a cured product with excellent low dielectric properties can be obtained, which is useful.

[0048] [Epoxy resin] The epoxy resin is not particularly limited, but is preferably, for example, a curable resin that contains two or more epoxy groups in the molecule and can be cured by forming a crosslinked network with the epoxy groups.

[0049] The epoxy resin is not particularly limited, but may be a novolac type epoxy resin such as a phenol novolac type epoxy resin, a cresol novolac type epoxy resin, an α-naphthol novolac type epoxy resin, a β-naphthol novolac type epoxy resin, a bisphenol A novolac type epoxy resin, or a biphenyl novolac type epoxy resin; Aralkyl-type epoxy resins such as phenol aralkyl-type epoxy resins, naphthol aralkyl-type epoxy resins, and phenol biphenyl aralkyl-type epoxy resins; Bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol AP type epoxy resin, bisphenol AF type epoxy resin, bisphenol B type epoxy resin, bisphenol BP type epoxy resin, bisphenol C type epoxy resin, bisphenol E type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, and tetrabromobisphenol A type epoxy resin; biphenyl-type epoxy resins such as biphenyl-type epoxy resins, tetramethylbiphenyl-type epoxy resins, and epoxy resins having a biphenyl skeleton and a diglycidyloxybenzene skeleton; Naphthalene type epoxy resin; Binaphthol type epoxy resin; Binaphthyl type epoxy resin; Dicyclopentadiene type epoxy resins such as dicyclopentadiene phenol type epoxy resins; glycidylamine-type epoxy resins such as tetraglycidyldiaminodiphenylmethane-type epoxy resins, triglycidyl-p-aminophenol-type epoxy resins, and diaminodiphenylsulfone-type glycidylamine-type epoxy resins; diglycidyl ester type epoxy resins such as 2,6-naphthalenedicarboxylic acid diglycidyl ester type epoxy resins and hexahydrophthalic anhydride glycidyl ester type epoxy resins; Benzopyran-type epoxy resins such as dibenzopyran, hexamethyldibenzopyran, and 7-phenylhexamethyldibenzopyran are included. Among these epoxy resins, so-called glycidyl ether type epoxy resins obtained by epoxidizing a phenol compound are preferred, and among these, novolac type epoxy resins, aralkyl type epoxy resins, and dicyclopentadiene type epoxy resins are more preferred from the viewpoint of dielectric properties.

[0050] The above-mentioned epoxy resins may be used alone or in combination of two or more kinds.

[0051] The epoxy equivalent of the epoxy resin is preferably 120 to 400 g / equivalent, more preferably 150 to 350 g / equivalent. When the epoxy equivalent of the epoxy resin is 120 g / equivalent or more, the dielectric properties of the resulting cured product are more excellent, and when the epoxy equivalent of the epoxy resin is 400 g / equivalent or less, the heat resistance and dielectric tangent of the resulting cured product are well balanced, which is preferable.

[0052] The softening point of the epoxy resin is preferably 20 to 200° C., and more preferably 40 to 150° C. When the softening point of the epoxy resin is 20° C. or higher, it is preferable that the epoxy resin has a fast curing property. On the other hand, when the softening point of the epoxy resin is 200° C. or lower, it is preferable that the epoxy resin has an excellent moldability.

[0053] The functional group (ester group) equivalent ratio (active ester / epoxy resin) of the amount of the active ester used to the amount of the epoxy resin used is preferably 0.1 to 5, and more preferably 0.5 to 4. When the functional group equivalent ratio is within the above range, the curability of the curable resin composition is further improved, the dielectric loss tangent of the obtained cured product is lower, and the heat resistance is further improved, which is preferable.

[0054] The curable resin composition of the present invention may further contain, in addition to the active ester and the epoxy resin, other curing agents, other resins, solvents, additives, etc., within the scope of not impairing the effects of the present invention.

[0055] [Other hardeners] In the curable resin composition of the present invention, other curing agents may be used in combination with the active ester.

[0056] The other curing agent is not particularly limited, but may include an amine curing agent, an acid anhydride curing agent, a phenol resin curing agent, and the like.

[0057] The amine curing agent is not particularly limited, but examples thereof include aliphatic amines such as diethylenetriamine (DTA), triethylenetetramine (TTA), tetraethylenepentamine (TEPA), dipropylenediamine (DPDA), diethylaminopropylamine (DEAPA), N-aminoethylpiperazine, menthenediamine (MDA), isophoronediamine (IPDA), 1,3-bisaminomethylcyclohexane (1,3-BAC), piperidine, N,N'-dimethylpiperazine, and triethylenediamine; and aromatic amines such as m-xylenediamine (XDA), methanephenylenediamine (MPDA), diaminodiphenylmethane (DDM), diaminodiphenylsulfone (DDS), benzylmethylamine, 2-(dimethylaminomethyl)phenol, and 2,4,6-tris(dimethylaminomethyl)phenol.

[0058] Examples of the acid anhydride curing agent include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol bistrimellitate, glycerol tristrimellitate, maleic anhydride, tetrahydrophthalic anhydride, methyl tetrahydrophthalic anhydride, endomethylene tetrahydrophthalic anhydride, methyl endomethylene tetrahydrophthalic anhydride, methylbutenyl tetrahydrophthalic anhydride, dodecenyl succinic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, succinic anhydride, and methylcyclohexene dicarboxylic anhydride.

[0059] Examples of the phenol resin curing agent include phenol novolac resin, cresol novolac resin, naphthol novolac resin, bisphenol novolac resin, biphenyl novolac resin, dicyclopentadiene-phenol addition type resin, phenol aralkyl resin, naphthol aralkyl resin, triphenol methane type resin, tetraphenol ethane type resin, and aminotriazine modified phenol resin.

[0060] The above-mentioned other curing agents may be used alone or in combination of two or more kinds.

[0061] [Other resins] The curable resin composition of the present invention may contain other resins in addition to the epoxy resin. In this specification, the term "other resins" refers to resins other than the epoxy resin.

[0062] Specific examples of the other resins include, but are not limited to, maleimide resins, bismaleimide resins, polymaleimide resins, polyphenylene ether resins, polyimide resins, cyanate ester resins, benzoxazine resins, triazine-containing cresol novolac resins, cyanate ester resins, styrene-maleic anhydride resins, allyl group-containing resins such as diallyl bisphenol and triallyl isocyanurate, polyphosphate esters, phosphate ester-carbonate copolymers, etc. These other resins may be used alone or in combination of two or more.

[0063] [solvent] The curable resin composition of the present invention may be prepared without a solvent or may contain a solvent. The solvent has a function of adjusting the viscosity of the curable resin composition.

[0064] Specific examples of the solvent include, but are not limited to, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ether-based solvents such as diethyl ether and tetrahydrofuran; ester-based solvents such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene, xylene, ethylbenzene, mesitylene, 1,2,3-trimethylbenzene, and 1,2,4-trimethylbenzene; and amide-based solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone. These solvents may be used alone or in combination of two or more.

[0065] The amount of the solvent used is preferably 10 to 90% by mass, and more preferably 20 to 80% by mass, based on the total mass of the curable resin composition. When the amount of the solvent used is 10% by mass or more, it is preferable because of excellent handleability. On the other hand, when the amount of the solvent used is 90% by mass or less, it is preferable from the viewpoint of economy.

[0066] [Additives] The curable resin composition of the present invention may contain additives, such as a curing accelerator, a flame retardant, and a filler.

[0067] (Cure accelerator) The curing accelerator is not particularly limited, but examples thereof include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and urea-based curing accelerators.

[0068] Examples of the phosphorus-based curing accelerator include organic phosphine compounds such as triphenylphosphine, tributylphosphine, tri-para-tolylphosphine, diphenylcyclohexylphosphine, and tricyclohexylphosphine; organic phosphite compounds such as trimethyl phosphite and triethyl phosphite; and phosphonium salts such as ethyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, butylphosphonium tetraphenylborate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylphosphine triphenylborane, tetraphenylphosphonium thiocyanate, tetraphenylphosphonium dicyanamide, butylphenylphosphonium dicyanamide, and tetrabutylphosphonium decanoate.

[0069] Examples of the amine curing accelerator include triethylamine, tributylamine, N,N-dimethyl-4-aminopyridine (DMAP), 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo[5.4.0]-undecene-7 (DBU), and 1,5-diazabicyclo[4.3.0]-nonene-5 (DBN).

[0070] Examples of the imidazole-based hardening accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4 ... Examples of the compound include ethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5 hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, and 2-methylimidazoline.

[0071] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-butylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, and 1-phenylbiguanide.

[0072] Examples of the urea-based curing accelerator include 3-phenyl-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, chlorophenylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, and 3-(3,4-dichlorophenyl)-1,1-dimethylurea.

[0073] Of the above-mentioned curing accelerators, it is preferable to use 2-ethyl-4-methylimidazole and N,N-dimethyl-4-aminopyridine (DMAP).

[0074] The above-mentioned curing accelerators may be used alone or in combination of two or more kinds.

[0075] The amount of the curing accelerator used can be appropriately adjusted to obtain the desired curability, but is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the total amount of the mixture of the epoxy resin and the active ester. When the amount of the curing accelerator used is 0.01 parts by mass or more, it is preferable because the curing property is excellent. On the other hand, when the amount of the curing accelerator used is 5 parts by mass or less, it is preferable because the insulation reliability is excellent.

[0076] (Flame retardant) The flame retardant is not particularly limited, but examples thereof include inorganic phosphorus-based flame retardants, organic phosphorus-based flame retardants, and halogen-based flame retardants.

[0077] The inorganic phosphorus-based flame retardant is not particularly limited, but examples thereof include red phosphorus; ammonium phosphates such as monoammonium phosphate, diammonium phosphate, triammonium phosphate, and ammonium polyphosphate; and phosphoric acid amides.

[0078] The organic phosphorus flame retardant is not particularly limited, but may be methyl acid phosphate, ethyl acid phosphate, isopropyl acid phosphate, dibutyl phosphate, monobutyl phosphate, butoxyethyl acid phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) phosphate, monoisodecyl acid phosphate, lauryl acid phosphate, tridecyl acid phosphate, stearyl acid phosphate. , isostearyl acid phosphate, oleyl acid phosphate, butyl pyrophosphate, tetracosyl acid phosphate, ethylene glycol acid phosphate, (2-hydroxyethyl) methacrylate acid phosphate and other phosphate esters; 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, diphenylphosphines such as diphenylphosphine oxide; 10-(2,5-dihydroxyphenyl)-10H-9-oxa -10-phosphaphenanthrene-10-oxide, 10-(1,4-dioxynaphthalene)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, diphenylphosphinylhydroquinone, diphenylphosphinyl-1,4-dioxynaphthalene, 1,4-cyclooctylenephosphinyl-1,4-phenyldiol, 1,5-cyclooctylenephosphinyl-1,4-phenyldiol and other phosphorus-containing phenols; 9,10-dihydro-9-oxa-10-phos cyclic phosphorus compounds such as 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,7-dihydroxynaphthyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, etc.; and compounds obtained by reacting the above-mentioned phosphate esters, the above-mentioned diphenylphosphine, or the above-mentioned phosphorus-containing phenols with epoxy resins, aldehyde compounds, or phenol compounds.

[0079] The halogen-based flame retardant is not particularly limited, but examples thereof include brominated polystyrene, bis(pentabromophenyl)ethane, tetrabromobisphenol A bis(dibromopropyl ether), 1,2-bis(tetrabromophthalimide), 2,4,6-tris(2,4,6-tribromophenoxy)-1,3,5-triazine, and tetrabromophthalic acid.

[0080] The above-mentioned flame retardants may be used alone or in combination of two or more kinds.

[0081] The amount of the flame retardant used is preferably 0.1 to 50 parts by mass, more preferably 1 to 30 parts by mass, relative to 100 parts by mass of the epoxy resin. When the amount of the flame retardant used is 0.1 parts by mass or more, it is preferable that flame retardancy can be imparted. On the other hand, when the amount of the flame retardant used is 50 parts by mass or less, it is preferable that flame retardancy can be imparted while maintaining dielectric properties.

[0082] (Filler) Examples of the filler include organic fillers and inorganic fillers. Organic fillers have the function of improving elongation and mechanical strength, etc. Inorganic fillers have the function of reducing the thermal expansion coefficient and imparting flame retardancy.

[0083] The organic filler is not particularly limited, but examples thereof include polyamide particles.

[0084] The inorganic filler is not particularly limited, but may be silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, zirconium tungstate phosphate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, carbon black, etc. Among these, it is preferable to use silica. In this case, as the silica, amorphous silica, fused silica, crystalline silica, synthetic silica, hollow silica, etc. may be used.

[0085] The filler may be surface-treated as necessary. In this case, the surface treatment agent that can be used is not particularly limited, but may be an aminosilane coupling agent, an epoxysilane coupling agent, a mercaptosilane coupling agent, a silane coupling agent, an organosilazane compound, a titanate coupling agent, or the like. Specific examples of the surface treatment agent include 3-glycidoxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, hexamethyldisilazane, and the like.

[0086] The above-mentioned fillers may be used alone or in combination of two or more kinds.

[0087] The amount of the filler used is preferably 0.5 to 95 parts by mass, more preferably 5 to 80 parts by mass, based on 100 parts by mass of the epoxy resin. If the amount of the filler used is 0.5 parts by mass or more, the effect of the filler can be sufficiently imparted, which is preferable. On the other hand, the amount of the filler used is preferably 95 parts by mass or less, so that the viscosity of the compound is not increased, which impairs the moldability.

[0088] <Cured product> The present invention relates to a cured product obtained by curing the curable resin composition. Since the active ester itself has a low dielectric tangent, the cured product obtained from the curable resin composition containing the active ester also has a low dielectric tangent, and the obtained cured product exhibits heat resistance, low dielectric properties, and a high elastic modulus due to suppression of warpage, which is a preferred embodiment.

[0089] As a method for obtaining a cured product by subjecting the curable resin composition to a curing reaction, for example, the heating temperature during heat curing is not particularly limited, but is preferably 100 to 300° C., and the heating time is preferably 1 to 24 hours.

[0090] <Uses of the curable resin composition> Examples of applications in which the curable resin composition is used include printed wiring board materials, resin compositions for flexible wiring boards, interlayer insulating materials for build-up boards, insulating materials for circuit boards such as adhesive films for build-up, resin casting materials, adhesives, semiconductor encapsulation materials, semiconductor devices, prepregs, conductive pastes, build-up films, build-up boards, fiber-reinforced composite materials, and molded products obtained by curing the above-mentioned composite materials. Among these various applications, in the applications of printed wiring board materials, insulating materials for circuit boards, and adhesive films for build-up, the composition can be used as an insulating material for so-called electronic component-embedded boards in which passive components such as capacitors and active components such as IC chips are embedded in the board. Furthermore, among the above, taking advantage of the characteristics of the cured product having excellent heat resistance, low dielectric properties, and high elastic modulus, the curable resin composition of the present invention is preferably used for semiconductor encapsulation materials, semiconductor devices, prepregs, flexible wiring boards, circuit boards, and build-up films, build-up boards, multilayer printed wiring boards, fiber-reinforced composite materials, and molded products obtained by curing the above-mentioned composite materials. A method for producing the semiconductor encapsulating material and the like from the curable resin composition will be described below.

[0091] 1. Semiconductor encapsulation materials The present invention relates to a semiconductor encapsulant containing the curable resin composition. As a method for obtaining a semiconductor encapsulant from the curable resin composition, the curable resin composition, a curing accelerator, and an inorganic filler are melt-mixed sufficiently until homogeneous using an extruder, kneader, roll, or the like as necessary. In this case, fused silica is usually used as the inorganic filler, but when used as a high thermal conductivity semiconductor encapsulant for power transistors and power ICs, it is preferable to use highly filled crystalline silica, alumina, silicon nitride, etc., which have a higher thermal conductivity than fused silica, or fused silica, crystalline silica, alumina, silicon nitride, etc. The filling rate is preferably in the range of 30 to 95 parts by mass per 100 parts by mass of the curable resin composition, and in particular, in order to improve flame retardancy, moisture resistance, and solder crack resistance and to reduce the linear expansion coefficient, it is more preferable to use 70 parts by mass or more, and even more preferable to use 80 parts by mass or more.

[0092] 2. Semiconductor Devices The present invention relates to a semiconductor device comprising a cured product obtained by heat-curing the semiconductor encapsulating material. A method for obtaining a semiconductor device from the curable resin composition includes molding the semiconductor encapsulating material by casting or using a transfer molding machine, an injection molding machine or the like, and further heating the material at 50 to 200°C for 2 to 10 hours.

[0093] 3. Prepreg The present invention relates to a prepreg having a reinforcing substrate and a semi-cured product of the curable resin composition impregnated into the reinforcing substrate. As a method for obtaining a prepreg from the curable resin composition, a method can be mentioned in which the curable resin composition is made into a varnish by blending the following organic solvent into a reinforcing substrate (paper, glass cloth, glass nonwoven fabric, aramid paper, aramid cloth, glass mat, glass roving cloth, etc.), and then heated at a heating temperature according to the type of solvent used, preferably 50 to 170 ° C. The mass ratio of the resin composition and the reinforcing substrate used at this time is not particularly limited, but it is usually preferable to prepare the resin content in the prepreg to be 20 to 60 mass %.

[0094] Examples of the organic solvent used herein include methyl ethyl ketone, acetone, dimethylformamide, methyl isobutyl ketone, methoxypropanol, cyclohexanone, methyl cellosolve, ethyl diglycol acetate, and propylene glycol monomethyl ether acetate. The selection and appropriate amount of the organic solvent used can be appropriately selected depending on the application. For example, when a printed circuit board is further produced from the prepreg as described below, it is preferable to use a polar solvent having a boiling point of 160° C. or less, such as methyl ethyl ketone, acetone, or dimethylformamide, and it is also preferable to use such a polar solvent in such a proportion that the nonvolatile content is 40 to 80 mass%.

[0095] 4. Circuit Board The present invention relates to a circuit board obtained by laminating the prepreg and copper foil, and subjecting the laminate to hot pressing and molding. A method for obtaining a printed circuit board from the curable resin composition includes laminating the prepreg by a conventional method, appropriately layering copper foil, and subjecting the laminate to hot pressing at 170 to 300°C under a pressure of 1 to 10 MPa for 10 minutes to 3 hours.

[0096] 5. Flexible wiring board The method for producing a flexible wiring board from the curable resin composition includes a method consisting of the following three steps: The first step is a step of applying a curable resin composition containing an active ester, an epoxy resin, and an organic solvent to an electrical insulating film using a coater such as a reverse roll coater or a comma coater, the second step is a step of heating the electrical insulating film to which the curable resin composition has been applied at 60 to 170°C for 1 to 15 minutes using a heater to volatilize the solvent from the electrical insulating film and to bring the curable resin composition to a B-stage, and the third step is a step of thermocompressing a metal foil to an adhesive using a heating roll or the like (the compression pressure is preferably 2 to 200 N / cm and the compression temperature is preferably 40 to 200°C) on the electrical insulating film to which the curable resin composition has been brought to a B-stage. If sufficient adhesive performance is obtained by going through the above three steps, the process may be terminated here, but if complete adhesive performance is required, it is preferable to further post-cure under conditions of 100 to 200° C. for 1 to 24 hours. The thickness of the curable resin composition film after final curing is preferably in the range of 5 to 100 μm.

[0097] 6. Build-up board The method for producing a build-up board from the curable resin composition includes a method consisting of the following three steps. The first step is a step of applying the curable resin composition, which is appropriately blended with rubber, filler, etc., to a circuit board on which a circuit is formed, using a spray coating method, a curtain coating method, etc., and then curing the composition. The second step is a step of forming a predetermined through-hole portion or the like as necessary, treating the surface with a roughening agent, washing the surface with hot water to form unevenness, and plating a metal such as copper. The third step is a step of repeating such operations in sequence as desired to alternately build up and form a resin insulating layer and a conductor layer of a predetermined circuit pattern. It is preferable to form a through-hole portion after forming the outermost resin insulating layer. The first step can be performed by laminating a build-up film that has been coated and dried to a desired thickness in advance, in addition to the above-mentioned solution coating. In addition, the build-up board of the present invention can be produced by forming a roughened surface by semi-curing the resin composition on the copper foil, and then heat-pressing the resulting resin-coated copper foil onto a wiring board having a circuit formed thereon at 170 to 250°C, thereby eliminating the need for a plating process.

[0098] 7. Build-up film The present invention relates to a build-up film containing the curable resin composition. The build-up film of the present invention can be produced by applying the curable resin composition to a support film to form a curable resin composition layer, thereby producing an adhesive film for a multilayer printed wiring board.

[0099] When producing a build-up film from a curable resin composition, it is essential that the film softens under the temperature conditions for lamination in a vacuum lamination method (usually 70 to 140°C) and exhibits fluidity (resin flow) that allows the resin to fill via holes or through holes present in the circuit board at the same time as lamination of the circuit board, and it is preferable to blend the above-mentioned components so as to exhibit such properties.

[0100] Here, the diameter of the through-holes in the multilayer printed wiring board is usually 0.1 to 0.5 mm, and the depth is usually 0.1 to 1.2 mm, and it is usually preferable to make it possible to fill the resin within this range. When both sides of the circuit board are laminated, it is preferable to fill about 1 / 2 of the through-holes.

[0101] Specifically, the adhesive film can be produced by preparing the curable resin composition in a varnish form, applying the varnish-like composition to the surface of the support film (Y), and then drying the organic solvent by heating or blowing hot air or the like to form a composition layer (X) made of the curable resin composition.

[0102] The thickness of the composition layer (X) formed is usually preferably equal to or greater than the thickness of the conductor layer. Since the thickness of the conductor layer of the circuit board is usually in the range of 5 to 70 μm, the thickness of the resin composition layer is preferably 10 to 100 μm.

[0103] The composition layer (X) in the present invention may be protected with a protective film described below. By protecting the resin composition layer with a protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be prevented.

[0104] Examples of the support film and protective film include polyolefins such as polyethylene, polypropylene, and polyvinyl chloride, polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate, polycarbonate, polyimide, and further release paper and metal foils such as copper foil and aluminum foil. The support film and protective film may be subjected to a release treatment in addition to a mud treatment and a corona treatment.

[0105] The thickness of the support film is not particularly limited, but is usually in the range of 10 to 150 μm, preferably 25 to 50 μm, and the thickness of the protective film is preferably 1 to 40 μm.

[0106] The above-mentioned support film (Y) is peeled off after laminating it onto the circuit board or after forming an insulating layer by heat curing. If the support film (Y) is peeled off after the adhesive film is heat cured, the adhesion of dust and the like during the curing process can be prevented. When peeling off after curing, the support film is usually subjected to a release treatment in advance.

[0107] 8. Multilayer printed wiring boards The film obtained as described above can also be used to manufacture a multilayer printed wiring board. In the method for manufacturing such a multilayer printed wiring board, for example, when the composition layer (X) is protected by a protective film, the protective film is peeled off, and then the composition layer (X) is directly laminated on one or both sides of the circuit board by, for example, a vacuum lamination method. The lamination method may be a batch method or a continuous method using a roll. In addition, the adhesive film and the circuit board may be heated (preheated) before lamination as necessary.

[0108] The lamination conditions are a pressure-bonding temperature (lamination temperature) of preferably 70 to 140°C and a pressure-bonding pressure of preferably 1 to 11 kgf / cm. 2 (9.8×10 4 ~107.9×10 4 N / m 2 ) and lamination is preferably performed under reduced pressure of 20 mmHg (26.7 hPa) or less.

[0109] 9. Fiber-reinforced composite materials A method for producing a fiber-reinforced composite material from the above-mentioned curable resin composition includes uniformly mixing each component constituting the curable resin composition to prepare a varnish, impregnating the varnish into a reinforcing base material consisting of reinforcing fibers, and then carrying out a polymerization reaction to produce the material.

[0110] Specifically, the curing temperature when carrying out such a polymerization reaction is preferably in the range of 50 to 250°C. In particular, it is preferable to carry out curing at 50 to 100°C to form a tack-free cured product, and then further treat it at a temperature of 120 to 200°C.

[0111] Here, the reinforcing fiber may be any of twisted yarn, untwisted yarn, and non-twisted yarn, but untwisted yarn and non-twisted yarn are preferred because they provide both moldability and mechanical strength of the fiber-reinforced plastic member. Furthermore, the form of the reinforcing fiber may be one in which the fiber direction is aligned in one direction or a woven fabric. For the woven fabric, a plain weave, a satin weave, or the like may be freely selected according to the part to be used and the application. Specifically, carbon fiber, glass fiber, aramid fiber, boron fiber, alumina fiber, silicon carbide fiber, and the like are excellent in mechanical strength and durability, and two or more of these may be used in combination. Among these, carbon fiber is particularly preferred because it provides good strength to the molded product, and various types of carbon fiber such as polyacrylonitrile, pitch, and rayon can be used. Among these, polyacrylonitrile-based carbon fibers are preferred because they can easily provide high-strength carbon fibers. Here, when the varnish is impregnated into a reinforcing base material made of reinforcing fibers to produce a fiber-reinforced composite material, the amount of reinforcing fibers used is preferably an amount such that the volume content of the reinforcing fibers in the fiber-reinforced composite material is in the range of 40 to 85%.

[0112] 10. Fiber-reinforced plastic moldings Examples of methods for producing a fiber-reinforced resin molded article from the curable resin composition include a hand lay-up method or a spray-up method in which fiber aggregates are laid in a mold and the varnish is multi-layered, a vacuum bag method in which a base material made of reinforcing fibers is impregnated with the varnish and molded by stacking it using either a male mold or a female mold, and a flexible mold capable of applying pressure to the molded article is placed over it to form an airtight seal and vacuum (reduced pressure) mold it, an SMC press method in which a sheet of varnish containing reinforcing fibers is compressed and molded in a mold, and an RTM method in which the varnish is injected into a mating mold in which fibers are laid out, to produce a prepreg in which the reinforcing fibers are impregnated with the varnish, and the prepreg is baked and hardened in a large autoclave. The fiber-reinforced resin molded article obtained above is a molded article having reinforcing fibers and a cured product of the curable resin composition. Specifically, the amount of reinforcing fibers in the fiber-reinforced resin molded article is preferably in the range of 40 to 70% by mass, and particularly preferably in the range of 50 to 70% by mass from the viewpoint of strength.

[0113] 11.Other Although the method for producing a semiconductor encapsulation material and the like has been described above, other cured products can also be produced from the curable resin composition. The other cured products can be produced according to a general curing method for a curable resin composition. For example, the heating temperature conditions may be appropriately selected depending on the type of curing agent to be combined, the purpose, and the like. EXAMPLES

[0114] The present invention will be described in detail below with reference to Examples and Comparative Examples. Note that the softening points and GPC charts of the active esters obtained below, and the heat resistance (glass transition temperature), dielectric properties (dielectric constant, dielectric tangent) and elastic modulus of the cured products obtained from the curable compositions containing the active esters were measured and evaluated under the following conditions.

[0115] <Softening point of active ester> The softening points (° C.) of the obtained active esters were measured according to JIS K7234 (ring and ball method).

[0116] <GPC Measurement> Measurement was carried out using the following measuring apparatus and measurement conditions, and GPC charts of the active esters obtained in the following synthesis examples, examples, etc. were obtained. From the results of the GPC charts, it was confirmed that the target product (active ester) was generated from the decrease and disappearance of the raw material peaks. Measuring apparatus: "HLC-8320 GPC" manufactured by Tosoh Corporation Column: Guard column "HXL-L" manufactured by Tosoh Corporation + "TSK-GEL G2000HXL" manufactured by Tosoh Corporation + "TSK-GEL G2000HXL" manufactured by Tosoh Corporation + "TSK-GEL G3000HXL" manufactured by Tosoh Corporation + "TSK-GEL G4000HXL" manufactured by Tosoh Corporation Detector: RI (differential refractometer) Data processing: "GPC Workstation EcoSEC-WorkStation" manufactured by Tosoh Corporation Measurement conditions: Column temperature 40 °C Developing solvent: Tetrahydrofuran Flow rate: 1.0 ml / min Standard: In accordance with the measurement manual of the "GPC Workstation EcoSEC-WorkStation", the following monodisperse polystyrenes with known molecular weights were used. (Polystyrene used) "A-500" manufactured by Tosoh Corporation "A-1000" manufactured by Tosoh Corporation "A-2500" manufactured by Tosoh Corporation "A-5000" manufactured by Tosoh Corporation "F-1" manufactured by Tosoh Corporation "F-2" manufactured by Tosoh Corporation "F-4" manufactured by Tosoh Corporation "F-10" manufactured by Tosoh Corporation "F-20" manufactured by Tosoh Corporation "F-40" manufactured by Tosoh Corporation "F-80" manufactured by Tosoh Corporation "F-128" manufactured by Tosoh Corporation Sample: A 1.0% by mass (solid content) tetrahydrofuran solution of the active ester obtained in the following Examples was filtered through a microfilter (50 μl) and used.

[0117] [Example 1] Synthesis of active ester (A-1) In a flask equipped with a thermometer, a dropping funnel, a cooling tube, a fractionating tube, and a stirrer, 220g (2.0 mol) of catechol, 144g (1.0 mol) of α-naphthol, and 2061g of toluene were charged, and the inside of the system was substituted with nitrogen under reduced pressure to dissolve. Next, 505g (2.5 mol) of isophthalic acid chloride was charged, and the inside of the system was substituted with nitrogen under reduced pressure to dissolve. Then, 1.0g of tetrabutylammonium bromide was dissolved, and while purging with nitrogen gas, the inside of the system was controlled to 60°C or less, and 1030g of a 20% by mass aqueous sodium hydroxide solution was dropped over 3 hours. Then, stirring was continued under these conditions for 1 hour. After the reaction was completed, the mixture was left to stand and separated, and the aqueous layer was removed. Furthermore, water was added to the toluene phase in which the reactants were dissolved, and the mixture was stirred and mixed for about 15 minutes, and the aqueous layer was left to stand and separated to remove. This operation was repeated until the pH of the aqueous layer reached 7. Thereafter, the mixture was dried under reduced pressure with heating to obtain 652 g of an active ester (A-1) represented by the following structural formula. The active ester (A-1) had an ester group equivalent of 137 g / equivalent, a softening point of 118° C., and a theoretical average number of repeating units n based on the charging ratio of the raw materials of 4. The number of repeating units n is preferably 1 to 10, more preferably 2 to 8, and further preferably 3 to 5. When the number of repeating units n is within the above range, high heat resistance, low dielectric constant, and low dielectric tangent are obtained, which is preferable. [ka]

[0118] [Example 2] Synthesis of active ester (A-2) The same procedure as in Example 1 was repeated except that 220 g (2.0 mol) of catechol in Example 1 was changed to 332 g (2.0 mol) of tert-butylcatechol, to obtain 759 g of active ester (A-2). The active ester (A-2) had an ester group equivalent of 160 g / equivalent, a softening point of 128° C., and a theoretical average number of repeating units n based on the charging ratio of the raw materials of 4. [ka]

[0119] [Example 3] Synthesis of active ester (A-3) 765 g of active ester (A-3) was obtained in the same manner as in Example 1, except that 220 g (2.0 mol) of catechol in Example 1 was changed to 332 g (2.0 mol) of tertiary butyl catechol and 144 g (1.0 mol) of α-naphthol was changed to 150 g (1.0 mol) of para-tertiary butyl phenol. The active ester (A-3) had an ester group equivalent of 161 g / equivalent, a softening point of 124° C., and a theoretical average number of repeating units n based on the charging ratio of the raw materials of 4. [ka]

[0120] [Comparative Example 1] Synthesis of active ester (A-4) In a flask equipped with a thermometer, a dropping funnel, a cooling tube, a fractionating tube, and a stirrer, 165g of a dicyclopentadiene and phenol weight-addition reaction resin (hydroxyl equivalent: 165g / equivalent, softening point 85°C), 72g (0.5 mol) of α-naphthol, and 630g of toluene were charged, and the system was purged with nitrogen under reduced pressure to dissolve. Next, 152g (0.75 mol) of isophthalic acid chloride was charged, and the system was purged with nitrogen under reduced pressure to dissolve. Then, 0.6g of tetrabutylammonium bromide was dissolved, and while purging with nitrogen gas, the system was controlled to 60°C or less, and 315g of a 20% by mass aqueous sodium hydroxide solution was dropped over 3 hours. Then, stirring was continued for 1 hour under these conditions. After the reaction was completed, the mixture was left to stand for separation, and the aqueous layer was removed. Furthermore, water was added to the toluene layer in which the reactant was dissolved, and the mixture was stirred and mixed for about 15 minutes, and the aqueous layer was left to stand for separation and removed. This procedure was repeated until the pH of the aqueous layer reached 7. The mixture was then dried under reduced pressure to obtain the active ester (A-4). The active ester (A-4) had an ester group equivalent of 223 g / equivalent and a softening point of 150°C.

[0121] [Examples 4 to 6 and Comparative Example 2] A bisphenol A type epoxy resin (DIC Corporation "850-S", epoxy equivalent: 188 g / equivalent) was used as the epoxy resin, the above-mentioned active esters (A-1) to (A-4) were used as the curing agent, and N,N-dimethyl-4-aminopyridine (DMAP) was used as the curing catalyst, and these were mixed in the composition shown in Table 1 below to obtain a curable composition. The obtained curable compositions were each poured into molds measuring 11 cm x 9 cm x 2.4 mm and 11 cm x 9 cm x 1.6 mm, and molded in a press at 180°C for 20 minutes. The molded products were then removed from the molds and cured at 175°C for 5 hours to obtain evaluation samples (cured products).

[0122] <Heat resistance (glass transition temperature)> The obtained cured product with a thickness of 2.4 mm was cut into a size of 5 mm width and 54 mm length, and this was used as a test piece to evaluate its heat resistance using a viscoelasticity measuring device (DMA: Rheometrics Corp. solid viscoelasticity measuring device "RSAII", rectangular tension method: frequency 1 Hz, heating rate 3°C / min). The temperature at which the ratio of the change in elastic modulus to the change in viscoelastic modulus was maximized (tan δ was largest), was defined as the glass transition temperature (Tg) (°C).

[0123] <Dielectric properties (dielectric constant, dielectric tangent)> The obtained cured product with a thickness of 1.6 mm was cut into a size of 2 mm width and 10 mm length, and these were used as test pieces. Using an Agilent Technologies Inc. network analyzer "E8362C", the dielectric constant and dielectric loss tangent at 1 GHz of the test pieces, which were heated and vacuum dried and then stored for 24 hours in a room at 23°C and 50% humidity, were measured using the cavity resonance method.

[0124] <Elasticity modulus> The obtained cured product with a thickness of 2.4 mm was cut into a size of 10 mm in width and 80 mm in length, and this was used as a test piece to determine the flexural modulus at room temperature using a universal testing machine ("AGI" manufactured by Shimadzu Corporation). Note that measurements were made with n=3, and the average value was used. In addition, the film thickness and width of the test piece were measured at 5 points, and the average value was used for calculation.

[0125] [Table 1]

[0126] From the evaluation results in Table 1 above, it was confirmed that the use of the desired active ester in Examples 4 to 6 resulted in excellent heat resistance, low dielectric properties (particularly low dielectric tangent), and high elastic modulus. On the other hand, in Comparative Example 2, the use of the desired active ester did not result in inferiority to the Examples in all evaluations. [Brief description of the drawings]

[0127] [Figure 1] 1 is a GPC chart of the active ester (A-1) obtained in Example 1. [Diagram 2] 1 is a GPC chart of the active ester (A-2) obtained in Example 2. [Diagram 3] 1 is a GPC chart of the active ester (A-3) obtained in Example 3.

Claims

1. The aromatic carboxylic acid is obtained by reacting an aromatic compound (a) having two hydroxyl groups at adjacent positions on an aromatic ring, an aromatic monohydroxy compound (b), and an aromatic compound having two or more carboxyl groups and / or an acid halide or ester thereof (c), The aromatic compound (a) is at least one compound selected from the group consisting of the following general formulas (1) to (3): 【Chemistry 1】 (In the above formula, each R independently represents a hydrocarbon group having 1 to 10 carbon atoms, n represents an integer of 0 to 4, and m represents an integer of 0 to 2.)

2. A curable resin composition comprising the active ester according to claim 1 and an epoxy resin.

3. A cured product obtained by subjecting the curable resin composition according to claim 2 to a curing reaction.

4. A prepreg comprising a reinforcing substrate and a semi-cured product of the curable resin composition according to claim 2 impregnated into the reinforcing substrate.

5. A circuit board obtained by laminating the prepreg according to claim 4 and copper foil, and subjecting the laminate to thermocompression molding.

6. A build-up film comprising the curable resin composition according to claim 2.

7. A semiconductor encapsulant comprising the curable resin composition according to claim 2.

8. A semiconductor device comprising a cured product obtained by heat-curing the semiconductor encapsulation material according to claim 7.

Citation Information

Patent Citations

  • Epoxy resin composition and its cured product

    JP2004169021A

  • Epoxy resin, production method, epoxy resin composition and cured product of same

    WO2017199831A1